2018
DOI: 10.1002/pc.25070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lithium chloride and in‐situ grafting on the performance of microcrystalline cellulose‐filled composites based on polyamide 6/high‐density polyethylene

Abstract: Polyamide 6 (PA6) and high-density polyethylene were blended with lithium chloride (LiCl) and maleic anhydride (MAH), and then mixed with 15 wt% microcrystalline cellulose to prepare the composites via hot-pressing technology. Crystallization analysis exhibited a decreased melting point of PA6 via the modification of LiCl. The crystallographic forms of PA6 were transformed from semi-crystalline to an amorphous state, thus decreased the processing temperature (from 240 to 200 C). Both LiCl and in-situ grafting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Xu et al. [ 29 ] reported a low melt point PA6/HDPE composite filled with microcrystalline cellulose by incorporating LiCl and found that the impact strength, flexural strength, and tensile strength of the composites with 1 wt% content of LiCl were improved simultaneously due to Li + ‐amide coordination. It can be speculated that introducing sacrificial bond into PA/rubber binary system may be a highly promising strategy to obtain outstanding toughness and strength at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al. [ 29 ] reported a low melt point PA6/HDPE composite filled with microcrystalline cellulose by incorporating LiCl and found that the impact strength, flexural strength, and tensile strength of the composites with 1 wt% content of LiCl were improved simultaneously due to Li + ‐amide coordination. It can be speculated that introducing sacrificial bond into PA/rubber binary system may be a highly promising strategy to obtain outstanding toughness and strength at the same time.…”
Section: Introductionmentioning
confidence: 99%